Letting people lead the way - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
People's self-development by Anisur Rahman 1993 234pp ISBN 1 85649 080 7 Pbk Zed Books Ltd 7 Cynthia Street London N1 9JF UK